What factors mediate the inter-relationship between frailty and pain in cognitively and functionally sound older adults? A prospective longitudinal ageing cohort study in Taiwan. Issue 2 (16th February 2018) - Chiou, Jing-Hui; Liu, Li-Kuo; Lee, Wei-Ju; Peng, Li-Ning; Chen, Liang-Kung
Abstract : Objectives: The main aim was to investigate the complex inter-relationship between frailty and pain, and the mediating roles of cognitive function, morbidity and mood in this nexus. Design: A cross-sectional analysis. Setting: A prospective community-dwelling population-based cohort. Participants: 1682 adults age ≥50 years without evident cognitive or functional impairment, or history of cancer. Primary and secondary outcome measures: The mediating effect of depression, cognitive function and comorbidity on the nexus between pain and frailty among older and middle-aged adults. Results: The pain score among older subjects (≥65 years), increased with the degree of frailty (robust=0.96±0.82; pre-frail=1.13±0.86; frail=1.63±1.02; P<0.001); multivariate analysis gave the same result, while moderate pain was associated with frailty in older subjects (OR=3.00, 95% CI 1.30 to 6.60). Conversely, pain and frailty among middle-aged subjects (aged 50–64 years) did not appear to be significantly related; in mediation analysis, pain exerted an indirect effect on frailty via depression (indirect effect=0.03, 95% CI 0.01 to 0.07), while neither cognitive function nor comorbidity had any significant effect in mediating the relationship between pain and frailty. Conclusion: In cognitively and functionally sound community-dwelling adults aged ≥50 years, moderate pain was related to frailty in those older than 65 years, but not younger ones. Besides the direct influence of pain on frailty, depression partially mediated the pain–frailty nexus. The mechanism by which depression influences pain and frailty requires further investigation.